TRPM4 keeps up the pace - Ambroziak, Wojciech; Siemens, Jan (Cell calcium, 2021)
The study by Li et al., provides a detailed pharmacological characterization of the ionic mechanisms that underlie rhythmic activity of retrotrapezoid nucleus neurons that control breathing. Specifically, the authors demonstrate a role of the transient receptor potential melastatin 4 (TRPM4) ion channel in the generation of subthreshold excitatory oscillations. Additionally, they propose that the ion channel contributes to tonic action potential (AP) firing - referred to as “pacemaking” - of these brainstem neurons with relevance for respiratory breathing and homeostasis in vivo.